Visiting the Modern Wunderkammer: Social-spatial Inequalities in Ways of Knowing - Etz, Sarah; Marguin, Séverine; Rabe, Henrike (Museum and Society, 2024)
Based on the assumption that museums have been spatially transformed in recent decades in the course of globalization, decolonization, and mediatization, we investigate from a socio-spatial perspective what influence this has on visitor experience and whether it leads to inequalities in ways of knowing. To this end, we conducted a visitor study in a science exhibition in a newly opened museum complex in Berlin, by using a mixed methods approach combining movement tracking, visitor survey and ethnographic observation. By analyzing the spatial practice in and spatial perception of the exhibition, we developed parameters along which spatial appropriation in the museum differs and correlated them with variables relating to museum spatial knowledge and scientific expertise. By integrating the spatial and social data using a multiple correspondence analysis protocol, we show that the legibility of museum space varies according to the visitors' cultural and specific symbolic-spatial capital. As this unequal access to the museum space has a direct influence on ways of knowing, the study shows that inequalities are reproduced by the current spatial refiguration of the museum.